U Pana Boga za piecem - Bromski, Jacek; Lenczewski, Ryszard; Wieczorkowski, Jan; Dzierma, Krzysztof; Beja-Zaborski, Andrzej
Life moves slowly in the quiet town on the eastern border of Poland, where everyone knows everyone and the very strict priest rules over all the citizens - even the mayor. But when a lovely, lonely Russian girl arrives, nothing will ever be the same again. [www.amazon.com]